2007
DOI: 10.1039/b713246h
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective and stereospecific acylation across oxirane- and silyloxy systems as a novel strategy to the synthesis of enantiomerically pure mono-, di- and triglycerides

Abstract: A trifluoroacetate-catalyzed opening of the oxirane ring of glycidyl derivatives bearing allylic acyl or alkyl functionalities with trifluoroacetic anhydride (TFAA), provides an efficient entry to configurationally homogeneous 1(3)-acyl- or 1(3)-O-alkyl-sn-glycerols. Selective introduction of tert-butyldimethylsilyl- (TBDMS), or triisopropylsilyl- (TIPS) transient protections at the terminal sites within these key intermediates secures 1(3)-acyl- or 1(3)-O-alkyl-3(1)-O-TBDMS (or TIPS)-sn-glycerols as general b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 119 publications
2
18
0
Order By: Relevance
“…In conclusion, we believe that the potential of SFC or the newly developed UPC 2 has not yet been exhausted. To our current knowledge, enantiomers of TAG have not yet been separated.…”
Section: Supercritical Fluid Chromatographymentioning
confidence: 89%
See 1 more Smart Citation
“…In conclusion, we believe that the potential of SFC or the newly developed UPC 2 has not yet been exhausted. To our current knowledge, enantiomers of TAG have not yet been separated.…”
Section: Supercritical Fluid Chromatographymentioning
confidence: 89%
“…However, the "optical activity" of these TAG is usually too low to be measured. For example, sn-1-oleoyl-2,3-dipalmitoyl-sn-glycerol (sn-O/P/P) has [a] D 20 ¼ 0.00 (c 7.05, CHCl 3 ) [2].…”
mentioning
confidence: 99%
“…The same applies to the optical properties such as optical rotation or ORD (optical rotatory dispersion), as their values approach zero. For instance, for 1-oleoyl-2,3-dipalmitoyl-sn-glycerol the [a] D 20 = 0.00 (c 7.05, CHCl 3 ) [32].…”
Section: Chiral-lc Of Synthetic Standardsmentioning
confidence: 99%
“…In the past five decades, only chemical (Stamatov and Stawinski, 2007;Vaique et al, 2010;Awl et al, 1989) and chemoenzymatic methods (Andrews et al, 2008;Haraldsson et al, 2000;Magnusson and Haraldsson, 2010) were reported for the synthesis of high regiopurity symmetrical TAGs with PUFAs at the sn-2 position in the literature. In these methods, many toxic solvents and reagents, such as 4-dimethylaminopyridine (DMAP), N-ethyl-N 0 -( 3-dimethylaminopropyl)-carbodiimide hydrochloride (EDCI) and fatty acid chloride were used.…”
Section: Introductionmentioning
confidence: 99%